The Hidden Burden in Antenatal Care: Determining the Level of Obstetric Violence and Its Associated Factors Among Pregnant Women - Kıymet Yeşilçiçek Çalık; Ebru Küçük Erdöl; Reyhan Erkaya (Journal of Advanced Nursing, 2026)
ABSTRACT Aim To determine the level of obstetric violence among pregnant women and identify associated sociodemographic and obstetric factors in Türkiye. Design A descriptive cross‐sectional study. Methods The study was conducted with 505 pregnant women attending antenatal clinics in Training and Research Hospitals in the Black Sea region of Türkiye between July and December 2025. Data were collected using a self‐administered sociodemographic form and the validated 18‐item Obstetric Violence Scale for Pregnant Women (OVS‐Pregnant Women). Total scale scores range from 0 to 72 (higher scores indicate higher perceived obstetric violence) across three subdimensions: Supportive Care and Information Support (0–28), Achieving Professional Standards of Care and Effective Communication (0–28), and Health Promotion and Encouragement (0–16). Data were analysed using descriptive statistics, and univariate and multivariate linear regression. Results The mean age of participants was 30.02 ± 5.46 years. The mean total OVS score was 16.681 ± 13.961 (out of 72). Subdimension mean scores were 9.853 ± 8.428 for Supportive Care and Information Support, 4.310 ± 4.314 for Achieving Professional Standards of Care and Effective Communication, and 2.516 ± 3.470 for Health Promotion and Encouragement. Multivariate analysis identified two factors independently associated with lower obstetric violence: family monthly wage above the minimum wage and receiving antenatal care at a training and research hospital. Conclusion Perceived obstetric violence scores were toward the lower end of the possible range, with socioeconomic status and healthcare institution type influencing women's care experiences. Implications for the Profession and/or Patient Care Obstetric violence should be recognized as a structural issue, necessitating standardized measurement tools and observational studies. Future studies should examine how exposure to obstetric violence shapes women's care preferences, informing patient‐centered interventions. Impact The findings provide actionable evidence for maternity care providers, hospital administrators, and healthcare policymakers to foster respectful, patient‐centered care. Reporting Method STROBE. Patient or Public Contribution No patient or public contribution.